делаем замену:
получим:
домножаем второе на 2
вычитаем из второго первое
5у=5
у=1
х=10-у=9
возвращаемся к замене:
b≠0 => a=b
подставляем b=a в первое:
a²=9
a²-9=0
(a-3)(a+3)=0
ответ (a,b)={ (3;3); (-3;-3))
- 3/2; 1/6.
Объяснение:
12y² + 16y - 3 = 0
D = b² - 4ac
D = 16² - 4 · 12 · (-3) = 256 + 144 = 400
х1/2 = -b ± √D x1/2 = -16 ± 20
2a 24
-16 - 20 -36 3
х₁ = = = -
24 24 2
-16 + 20 4 1
х₂ = = =
24 24 6
делаем замену:
получим:
домножаем второе на 2
вычитаем из второго первое
5у=5
у=1
х=10-у=9
возвращаемся к замене:
b≠0 => a=b
подставляем b=a в первое:
a²=9
a²-9=0
(a-3)(a+3)=0
ответ (a,b)={ (3;3); (-3;-3))